(3GdefJbi ef JGQjN GdESdGe ddPgHis - (3CMeO Hf GdedG eMeO Hf Ydj Hf CMeO GdTGaYjs; (3GdPgHj,J (B748 (3g` s
(3ChdgG (B:s
(3ef SfI (B451(3g` s
(3BNQgG (B:s
(3Edi SfI (B530(3g` s
(3ef SfI (B451- (3SfI (B530(3g`s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B162 s
Keywords: (3GdJGQjNs